Association of Drinking Water and Enteric Fever: A Disguised Source of Infection - Fatima Tuz Zahra, Sidrah Saleem, Muhammad Imran, Nida Javed, Ayesha Ghazal, Saadia Ch (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Enteric fever is an illness caused by Salmonella enterica serovars Typhi and Paratyphi A and B. The mode of transmission is the ingestion of contaminated food and water. Aim: To check that whether drinking water is the source of infection or not. Methodology: 202 water samples were collected from the various areas of Lahore. 120 samples were taken from houses and the neighbourhood of confirmed typhoid patients and 82 samples were randomly collected. The samples were centrifuged, enriched and then subcultured on XLD media. The isolated colonies were identified by biochemical reactions. The sero-typing confirmed Salmonella species were done. Results: The results showed that 23% of the drinking water in Lahore was fit for drinking, 76% samples were contaminated. The organisms isolated were Serratia spp. 22%, Enterobacter spp. 22%, E. coli 16%, Citrobacter spp. 12%, Pseudomonas spp. 9%, Proteus spp. 6%, Klebsiella spp. 4%, Salmonella Paratyphi A and Salmonella Rubislaw as 1%. No Salmonella Typhi was isolated from any water sample. Conclusion: The presences of large coliforms in drinking water were indicative of sewerage contamination. The Salmonella Paratyphi A might be source of infection in that specific area but overall the results suggested that drinking water of Lahore was not acting as a source of infection for Enteric caused by Salmonella Typhi.